2016
DOI: 10.4251/wjgo.v8.i9.688
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum vitamin D levels and gastric cancer: A retrospective chart analysis

Abstract: AIMTo determine whether there is an increased risk of gastric adenocarcinoma associated with vitamin D deficiency (VDd).METHODSA retrospective case control study was performed of all patients diagnosed with gastric adenocarcinoma between 2005 and 2015. After we excluded the patients without a documented vitamin D level, 49 patients were included in our study.RESULTSThe average age of patients with gastric adenocarcinoma and documented vitamin D level was 64 years old (95%CI: 27-86) and average vitamin D level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…The only non-significant finding for six quantiles of 25(OH)D concentration was an increased risk for pancreatic cancer at the highest quantile. In other studies, reduced risk was evident for gastric (59), kidney (45), and ovarian cancer (82). Why no inverse correlations with respect to 25(OH)D concentration was present for those cancers in the VDPP study is unclear.…”
Section: The Cohort Consortium Vitamin D Pooling Project Of Rarer Canmentioning
confidence: 72%
“…The only non-significant finding for six quantiles of 25(OH)D concentration was an increased risk for pancreatic cancer at the highest quantile. In other studies, reduced risk was evident for gastric (59), kidney (45), and ovarian cancer (82). Why no inverse correlations with respect to 25(OH)D concentration was present for those cancers in the VDPP study is unclear.…”
Section: The Cohort Consortium Vitamin D Pooling Project Of Rarer Canmentioning
confidence: 72%
“…Since retrospective studies have demonstrated an association between hypovitaminosis D (vitamin D insufficiency and deficiency) and gastric adenocarcinoma, low vitamin D levels may also be associated with other steps in the carcinogenetic pathway [ 10 , 11 , 12 ]. However, no study has yet assessed associations between hypovitaminosis D and pre-malignant histopathological changes in the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the presence or absence of gastric incomplete intestinal metaplasia after gastric biopsy, patients were designated as either a control (no gastric intestinal metaplasia) or case (gastric intestinal metaplasia) subject. Serum 25-hydroxyvitamin D levels were classified according to definitions established by the Endocrine Society: 30–100 ng/dL was considered normal, with insufficient 25-hydroxyvitamin D levels or hypovitaminosis D subgrouped into two: vitamin D insufficiency (VDi; 20–29 ng/dL) and vitamin D deficiency (VDd; <20 ng/dL) [ 12 , 15 ]. Two categories were used to assess timing of vitamin D collection: fall-winter representing times of less daylight exposure (fall months included September, October, and November, and winter months included December, January, and February) and spring-summer, representative of months with more daylight exposure (spring months included March, April, and May, and summer months included June, July, and August).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later in the disease phase, there is bleeding which leads to anemia. [15] Vitamin D plays an important role during tumorigenesis. Increased levels of serum Vitamin D reduce the risk of gastric cancer.…”
Section: Esophageal Cancermentioning
confidence: 99%